2020
DOI: 10.3389/fgene.2020.00729
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Mutational Hotspots of Plastomes in Debregeasia (Urticaceae)

Abstract: Debregeasia is an economically important genus of the nettle family (Urticaceae). Previous systematic studies based on morphology, or using up to four plastome regions, have not satisfactorily resolved relationships within the genus. Here, we report 25 new plastomes for Urticaceae, including 12 plastomes from five Debregeasia species and 13 plastomes from other genera. Together with the one published plastome for Debregeasia, we analyzed plastome structure and character, identified mutation hotspots and loci u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 57 publications
9
16
0
Order By: Relevance
“…However, the 3′ ends are found in the IRa and IRb regions. These results are similar to those in other species in Urticaceae [ 22 ].
Fig.
…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, the 3′ ends are found in the IRa and IRb regions. These results are similar to those in other species in Urticaceae [ 22 ].
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…Although the plastid genome is highly conserved, some interesting structural variations have been observed in some taxa, such as the rare expansion of IR regions in Strobilanthes [15], the insertion of mitochondrial DNA in the plastome of Anacardium [19], and the complete or partial loss of IR regions in some legumes [16,20,21]. In a recent study, Wang et al reported plastid genomes from 13 of 58 genera in Urticaceae, providing an abundance of plastid genome resources for the study of this group of plants [22]. Unfortunately, there have been no reports on the plastid genome of Pilea plants.…”
Section: Introductionmentioning
confidence: 99%
“…However, the 3' ends are found in the IRa and IRb regions. These results are similar to those in other species in Urticaceae [22].…”
Section: Genome Annotationsupporting
confidence: 91%
“…Plastome provides sufficient information to resolve the phylogenetic relationships at generic and infrageneric level. Despite several plastid genomes of species in Urticaceae have been reported (Wu et al 2017;Wu et al 2018;Fu et al 2019;Wang et al 2020), none of them belong to Procris.…”
mentioning
confidence: 99%